PS-P06-6: GENDER DIFFERENCES ON DETERMINANTS OF GOOD KNOWLEDGE ON RECOGNITION OF STROKE SYMPTOMS AND ACTIONS DURING A STROKE AMONG HYPERTENSIVE PATIENT. (January 2023) - Ching, Siew Mooi; Chia, Yook Chin; Devaraj, Navin Kumar; Lim, Hooi Min; Beh, Hooi Chin
Abstract : Early recognition and action during a stroke are extremely important to improve stroke prognosis. This study aimed to examine the gender difference in the KAP of stroke in hypertensive patients. This was a cross-sectional study conducted on adults 18 years and older who participated in a community blood pressure (BP) screening program in Malaysia during MMM2017. The questionnaire was derived based on the acronym F.A.S.T recommended by the American Stroke Association and two common symptoms of middle cerebral artery occlusion (paralysis of one side of the body and numbness or tingling sensation of one side of the body). Using multivariate logistic regression, the determinants of recognizing stroke symptoms and knowing what to do during a stroke in female and male hypertensive patients were identified. Among 1019 hypertensive patients, 85.% of women versus 84% of men were able to recognise symptoms of stroke (p = 0.564) but the prevalence of good knowledge of actions to be taken by being hospitalised within 4.5 hours during a stroke was 74% among women vs. 80% in men (p = 0.05). Using multivariate logistic regression, the determinants for recognising stroke symptoms among male hypertensive patients were age more than 45 year old(OR: 2.670, p = 0.016) compared with those aged below 45, symptom of body paralysis (OR: 9.37, p = 0.001) and symptom of numbness of the body(OR:6.177, p < 0.001);whereas in female hypertensive patient were symptoms of body paralysis (OR:26.582, p < 0.001), being Malay (OR:2.306, p = 0.034) vs. non-Malay and age more than 45 year old(OR:2.706, p = 0.024) compared to those under 45 years old. The determinants of good knowledge on actions to be taken during a stroke among male hypertensive patient were symptoms of body paralysis (OR:8.25, p = 0.031) compared to female respondents were symptom of body paralysis (OR:5.603, p < 0.001), symptom of slurred speech (OR:5.597, p = 0.003) and diastolic BP (OR:0.962, p = 0.005). Men know better what to do during a stroke. Symptoms of body paralysis was the most common stroke symptoms recognized by all hypertensive patients regardless in order to take further action. Clinicians need to be aware of these findings, and more action needs to be taken to educate female hypertensive patients about other stroke symptoms so that further action can be taken.